2020
DOI: 10.1186/s12944-020-01219-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of MicroRNAs expressed in perirenal adipose tissue during rabbit growth

Abstract: Background MicroRNAs (miRNAs) regulate adipose tissue development, which are closely related to subcutaneous and intramuscular fat deposition and adipocyte differentiation. As an important economic and agricultural animal, rabbits have low adipose tissue deposition and are an ideal model to study adipose regulation. However, the miRNAs related to fat deposition during the growth and development of rabbits are poorly defined. Methods In this study, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…miRNA from 21 to 24 nt were responsible for 88%−92% of all reads in each library ( Figure 1 ), reflecting miRNA plurality. Moreover, predominant miRNAs in libraries were 22-nt long, consistent with earlier findings from other research with rabbit ( 39 ), pig ( 40 ) and cow ( 41 ). Thus, nine miRNA libraries developed from rabbit tissues were technically reliable and suitable for subsequent investigation.…”
Section: Discussionsupporting
confidence: 91%
“…miRNA from 21 to 24 nt were responsible for 88%−92% of all reads in each library ( Figure 1 ), reflecting miRNA plurality. Moreover, predominant miRNAs in libraries were 22-nt long, consistent with earlier findings from other research with rabbit ( 39 ), pig ( 40 ) and cow ( 41 ). Thus, nine miRNA libraries developed from rabbit tissues were technically reliable and suitable for subsequent investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Through the functional enrichment analysis of DE mRNA, we found that these DE mRNA could be classified into six categories: Cellular Processes, Genetic Information Processing, Environmental Information Processing, Human Diseases, Metabolism and organic Systems. The functional attributes of genes and their expression level in organs or cells are important factors to determine their function realization ( 42 ). When we excluded some genes with low FPKM, we further obtained that 54 DE mRNAs may play the key roles in lipid metabolism during the growth and development of liver, including EPHX1, ACSS2 and CYP39A1 , which were continuously up-regulated in four growth stages, and LDHB, CA2, ELOVL2 , which were continuously down-regulated, and these DE mRNAs were regulated by 249 lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Tianfu Black rabbits (native species in Sichuan province of China) were raised at the breeding center of Sichuan Agricultural University, Ya’an, China. These rabbits were breast-fed before 30 days and then fed with the same standard diet (a commercial pelleted food (16% protein, 10.8 MJ/kg)) as described in our previous study after weaning ( Wang G. et al, 2020 ) and water ad libitum . Interscapular adipose tissues were collected from 12 male rabbits at different growth stages of 0 days (D0), D15, D85, and 2 years (Y2) (three individuals per stage), which represent the infant stage, early whitening stage, puberty stage, and elder stage, respectively.…”
Section: Methodsmentioning
confidence: 99%